2016
DOI: 10.1590/0034-7167.2016690117i
|View full text |Cite
|
Sign up to set email alerts
|

Práticas de exposição e proteção solar de jovens universitários

Abstract: although the sample was made up of people with greater access to information, it was found exposure and sunscreen improperly. Education, individual and collective actions should be strengthened and prioritized given the incidence of skin cancer in the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
2
7
0
4
Order By: Relevance
“…Among the low number of individuals that reported using sunscreen with the adequate frequency, a considerable portion reported using products with SPF<15 or not having information regarding SPF coverage or the UVA/UVB protection spectrum of the sunscreen, indicating that the reported some protection might not be effective against the harmful spectrum of solar radiation. Urasaki (2016) reported that more than 40% of the university students interviewed used SPF<15, 7 in accordance to our study. The students in group 2 were again associated to unfavorable results since almost half of them did not even know the features of the sunscreens they used.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Among the low number of individuals that reported using sunscreen with the adequate frequency, a considerable portion reported using products with SPF<15 or not having information regarding SPF coverage or the UVA/UVB protection spectrum of the sunscreen, indicating that the reported some protection might not be effective against the harmful spectrum of solar radiation. Urasaki (2016) reported that more than 40% of the university students interviewed used SPF<15, 7 in accordance to our study. The students in group 2 were again associated to unfavorable results since almost half of them did not even know the features of the sunscreens they used.…”
Section: Discussionsupporting
confidence: 90%
“…Data from the literature show that the information that young people have in this respect do not generally come from health professionals, therefore, a scenario that can be modified. 7 , 13 , 14 On the other hand, when considering that the evaluated knowledge was extremely basic, it is worrisome that more than 10% of the sample had an unsatisfactory knowledge. University students represent a portion with unique education regarding the general population in which the lack of photo-educational knowledge tends to be even more frequent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso, o uso regular de protetor solar foi relatado em apenas 15% dos jovens. Nesse estudo, 50% relataram usar somente em dias ensolarados e 67% referiram nunca reaplicar o produto (BELLETTI, 2016).…”
Section: Introductionunclassified